A 'post-close' Technique for Femoral Hemostasis After Percutaneous EVAR Using an Ultra-low-profile Endoprosthesis System. (2015) - Chaudhuri, A.
Abstract : Introduction: We present a 'post-close' technique using the Angio-Seal VIP vascular closure device (VCD) after percutaneous endovascular aneurysm repair (p-EVAR) using an ultra-low-profile (ULP) device. Technique: Following percutaneous using an ULP device (here the Ovation Prime system, Trivascular, Eysins, Switzerland), contralateral femoral hemostasis is achieved by using an 'undersized' application of an 8F Angio-Seal VIP vascular closure device (VCD) for all punctures wherein upto 12F sheaths have been applied for access. On the ipsilateral side, following 'double-wire' preparation, synchronous deployment of an 8F and 6F Angio-Seal VIP VCDs achieves hemostasis. Procedural heparin is reversed as an adjunct, pressure dressings are applied and the patient kept flat for 2 hours. Discussion: Double-wire VCD deployments, and 'post-close' techniques have not been described in the context of femoral hemostasis after p-EVAR. This technique is easy to apply and saves time (and potentially cost) used to set up 'pre-close' devices, as is typically used these days.